Massive stars exploding in a He-rich circumstellar medium XII. SN 2024acyl: A fast, linearly declining Type Ibn supernova with early flash-ionisation features - Cai, Y. -Z.; Pastorello, A.; Maeda, K.; Zhao, J. -W.; Wang, Z. -Y.; Peng, Z. -H.; Reguitti, A.; Tartaglia, L.; Filippenko, A. V.; Pan, Y.; Valerin, G.; Kumar, B.; et al. (EDP Sciences, 2026)
We present a photometric and spectroscopic analyses of the Type Ibn supernova (SN) 2024acyl. It rises to an absolute magnitude peak of Mo = −17.58 ± 0.15 mag in 10.6 days, and displays a rapid linear post-peak light-curve decline in all bands (e.g. γ0 − 60(V) = 0.097 ± 0.002 mag day−1), similar to most SNe Ibn. The optical pseudobolometric light curve peaks at (3.5 ± 0.8)×1042 erg s−1, with a total radiated energy of (5.0 ± 0.4)×1048 erg. The spectra are dominated by a blue continuum at early stages, with narrow P-Cygni He I lines and flash-ionisation emission lines of C III, N III, and He II. The P-Cygni He I features gradually evolve and become emission-dominated in late-time spectra. The Hα line is detected throughout the entire spectral evolution, which indicates that the circumstellar material (CSM) is helium-rich with some residual amount of hydrogen. Our multi-band light-curve modelling yields estimates of the ejecta mass of Mej = 0.49+0.11−0.09 M⊙ with a kinetic energy of Ek = 0.06+0.01−0.01 × 1051 erg, and a 56Ni mass of MNi = 0.018 M⊙. The inferred CSM properties are characterised by a mass of MCSM = 0.51+0.05−0.04 M⊙, an inner radius of R0=17.8+3.6−3.0 AU, and a density of ρCSM = (8.3+2.7−1.2) × 10−12 g cn−3. The multi-epoch spectra are well reproduced by the CMFGEN/ he4p0 model, corresponding to a He-ZAMS mass of 4 M⊙ (H-ZAMS mass 18.11 M⊙, pre-SN mass 3.16 M⊙). These findings are consistent with a scenario of an SN powered by ejecta-CSM interaction originating from a low-mass helium star that evolved within an interacting binary system where the CSM with some residual hydrogen may originate from the mass-transfer process. We also discuss an extreme scenario involving the possible merger of a helium white dwarf. In addition, a channel of core-collapse explosion of a late-type Wolf-Rayet (WR) star with hydrogen, or a transitional star between an Of and a WR type (e.g. an Ofpe/WN9 star) with fallback accretion cannot be entirely ruled out.